Interfacial Thermal Transport in Monolayer MoS2‐ and Graphene‐Based Devices. Issue 17 (13th July 2017) - Yasaei, Poya; Foss, Cameron J.; Karis, Klas; Behranginia, Amirhossein; El‐Ghandour, Ahmed I.; Fathizadeh, Arman; Olivares, Javier; Majee, Arnab K.; Foster, Craig D.; Khalili‐Araghi, Fatemeh; Aksamija, Zlatan; Salehi‐Khojin, Amin
Abstract : In many device architectures based on 2D materials, a major part of the heat generated in hot‐spots dissipates in the through‐plane direction where the interfacial thermal resistances can significantly restrain the heat removal capability of the device. Despite its importance, there is an enormous (1–2 orders of magnitude) disagreement in the literature on the interfacial thermal transport characteristics of MoS2 and other transition metal dichalcogenides (TMDs) (0.1–14 MW m −2 K −1 ). In this report, the thermal boundary conductance (TBC) across MoS2 and graphene monolayers with SiO2 /Si and sapphire substrates is systematically investigated using a custom‐made electrical thermometry platform followed by 3D finite element analyses. Through comparative experiments, the TBC at 295 K across MoS2 is found to be 20.3–33.5 MW m −2 K −1 on SiO2 /Si, and 19–37.5 MW m −2 K −1 on c‐sapphire, respectively, but far larger than the previous Raman‐based measurements on TMDs with optical heating (0.1–2 MW m −2 K −1 ). This study also investigates the effects of processing quality and potential interface contaminants, substrate properties, and encapsulation on TBC across MoS2 and graphene monolayers. Our results reveal that the emergence of Rayleigh wave modes dramatically contributes to the interfacial conductance across encapsulated 2D monolayers. This finding opens up an additional pathway to improve heat dissipation in 2D‐based devices through engineering of an encapsulating layer. Abstract : Thermal transport across MoS2 and graphene monolayers is investigated through a combination of experiments, simulations, and modeling. The thermal boundary conductance (TBC) across MoS2 at 295 K is found to be 20.3–33.5 MW m −2 K −1 on SiO2 /Si, and 19–37.5 MW m −2 K −1 on c‐sapphire, respectively. This study also unveils that TBC is remarkably affected by encapsulation due to phonon mode hybridization and emergence of Rayleigh waves.